THE LANDSCAPE ATTRIBUTES IN THE SEPOTUBA RIVER BASIN IN MATO GROSSO, BRAZIL - Gamero, Alessandra Rodrigues; Neves, Sandra Mara Alves da Silva; Leandro, Gustavo Roberto dos Santos [UNESP]; Galvanin, Edineia Aparecida dos Santos [UNESP]; Gonzalez, Alfredo Zenen Dominguez (Univ Estadual Paulista Julio Mesquita Filho, 2023)
This study aims to analyse the main landscape attributes in the Sepotuba River basin as well as the influence of land use in its environmental conservation. The methodology procedures employed were: bibliographical and documentary research; thematic mapping in Geographical Information System; quantification of the themes' attributes and analysis of generated data. The Sepotuba river basin is an environment susceptible to environmental degradation considering its geomorphical compartments above all, in the river - floodplain system, whose lithology is made up of consolidated sediments of the Pantanal Formation and Present-day Alluvial. In terms of vegetation cover, there is a predominance of forest formations scattered throughout the Amazon, Cerradi and Pantanal biomes. It can also be seen in the study area that its compartmentalization in relation to the longitudinal profiles of its affluents. That's because there are stretches of the river system that run through the Chapada and the Parecis Plateau well-defined by an escarpment system and stretches that go into the plains and swamps. As for the land occupation, it has been possible to observe the removal of most of vegetation cover converted into areas of farming use. Hence, the replacement of vegetation cover, soil exposure to erosion sediment input into the river system have been jeopardised the maintenance of environmental quality in the Sepotuba River basin.
Keywords: Physical Environmental Aspects; Geotechnology; Environmental Conservation; Anthropisation; Mato Grosso